Extracellular peptidase and carbohydrate hydrolase activities in an Arctic fjord (Smeerenburgfjord, Svalbard) - Steen, Andrew D.; Arnosti, Carol (2013)
Measurements of the spectrum of extracellular enzymes present in an environment can indicate the nature of organic substrates available to microorganisms. We report the activities in an Arctic fjord (Smeerenburgfjord, Svalbard) of the extracellular carbohydrate hydrolases a-galactosidase, β-glucosidase, and chitobiase, and the extracellular peptidases leucyl aminopeptidase, trypsin, and chymotrypsin. Among the carbohydrate hydrolases, β-glucosidase had the highest potential activity. Although extracellular leucyl aminopeptidase is frequently assayed in marine systems, activities of other peptidases have only rarely been reported. Peptidase activities were higher than carbohydrate hydrolase activities by approximately 2 orders of magnitude. Activities of leucyl aminopeptidase (an exopeptidase which cleaves terminal residues from a protein) were higher than trypsin and chymotrypsin (both endopeptidases which cleave interior bonds). In contrast to previous measurements from coastal, temperate environments, potential activity of leucyl aminopeptidase in Smeerenburg was higher than that of the endopeptidases trypsin and of chymotrypsin. These results suggest that leucyl aminopeptidase may not always be a reliable proxy for the total peptidolytic potential of microbial communities.